Features of the Legal Status of Women in the Traditional Society of the Peoples of the Caucasus of the 18th and 19th Centuries - M. A. Bagapsh; S. B. Glushachenko (Теоретическая и прикладная юриспруденция)
The history of traditional societies constantly attracts the attention of the research community. The interest of both domestic and foreign scientists is observed both in early historical times and at the present stage. Among the issues of great interest to researchers are the peculiarities of the legal status of women in the traditional society of the peoples of the Caucasus of the XVII–XIX centuries. The author substantiates the relevance and significance of the research topic. The purpose of the article is to identify the features of the legal status of women in the traditional society of the peoples of the Caucasus of the XVII–XIX centuries. The article uses general scientific and specific methods of historical and historiographical research, including methods of objectivity and comparative analysis. The article analyzes the specific features of the legal vulnerability of women of the peoples of the Caucasus, in this regard, the status of the status of women according to Adat and Sharia seems interesting. The article provides a brief justification of the role and significance of the development of customary law, since a dual system of customary law (adat) and Sharia has developed in the Caucasus. The analysis of the scientific literature allowed us to conclude that the absence of a state system and state law contributed to the long-term preservation of the adat in the Caucasus. It is postulated that there are three types of customary law: customary law before the reformation (from the XV to the XIX centuries), reformed customary law (from the second half of the XIX to the beginning of the XX centuries) and customary law of the Soviet and post-Soviet period (from 1920 to the 1990s). The article also examines the peculiarities of property and inheritance rights, as well as the formation of feminism as a social movement for women’s rights in the traditional society of the peoples of the Caucasus of the XVII–XIX centuries. The author comes to the conclusion that it is necessary to further improve institutional mechanisms to ensure compliance with Sharia and Adat laws.